Towards sustainable mining: apropos of the new environmental protection regulation for mining exploration activities - Reyes Asencio, Antuanet (2019)
The recent Environmental Protection Regulation for Mining Exploration Activities has brought with it a sequence of modifications and technical classifications in the stages of the mining activity that directly aff ect the issuance of mining licenses.In this article, the author seeks to analyze and explain if these modifications contribute to the dynamism of the mining exploration activity and generate a friendly regulation for both the investor and the environment.